Lexical and grammatical cohesion analysis in “clouds” song lyrics - Dewi, Luh Gede Ayu Krisna Sari (Yayasan Mitra Persada Nusantara, 2023)
The objective of the study is to investigate and describe the lexical and grammatical devices as cohesion in Zach Sobiech's song